A Study on Risk and Expense Evaluation of Agility Supply Management of Machinery - Mohammad Heydari; Kin Keung Lai (Discrete Dynamics in Nature and Society)
We provide a technical assessment and critique of the existing literature via highlighting problems associated with conceptualization and technical improvement of agility practices. By presenting a narrative evaluation of the technical review, we underscore the nature of the SC hazard in addition to agility practices and furnish a synthesis for future studies. The purpose is to examine the relationship between identifying and ranking the elements affecting supply management for SC agility in compressed natural gas pressure vessels. This study is applied research and data are collected based on descriptive survey. The populace of the investigation is milled compressed natural gas pressure vessels. Survey data are amassed through interviews and questionnaires. Cronbach’s alpha has been utilized to evaluate the reliability of the values received 0.778, which shows that the questionnaire is of excellent reliability and the questionnaire has 27 questions. Also, because the volume of the statistical population is 270 people, the consequences show that there is a positive connection among the empowerment of SC agility. Driving agility is on a positive supply chain (SC) agility. The expense has a poagilitysitive impact on SC agility.